The mechanics of central bank intervention in foreign exchange markets - Kaushik Basu (Cornell University, Center for Analytical Economics (CAE), 2009)
Central banks in developing countries, wanting to devalue the domestic currency, usually intervene in the foreign exchange market by buying up foreign currency using domestic money-often backing this up with sterilization to counter inflationary pressures. Such interventions are usually effective in devaluing the currency but lead to a build up of foreign exchange reserves beyond what the central bank may need. The present paper analyzes the mechanics of such central bank interventions and, using techniques of industrial organization theory, proposes new kinds of interventions which have the same desired effect on the exchange rate, without causing a build up of reserves.
Keywords: L31; D43; F31; G20; 330; exchange rate; oligopoly theory; central bank intervention; foreign exchange dealers; India; Wechselkurspolitik; Währungsreserven; Devisenmarkt; Oligopol; Indien; Entwicklungsländer